Beneficial Soil Fungi Isolated from Tropical Fruit Crop Systems for Enhancing Yield and Growth in Dragon Fruit in Ecuador - Yoansy Garcia; Danilo Valdez; Daniel Ponce de Leon; Hypatia Urjilez; Jaime Santos-Pinargote; Daniel Mancero-Castillo (International Journal of Plant Biology, 2025)
Rhizospheric fungi are emerging as a critical research component in dragon fruit (Hylocereus spp.) production systems. Introducing beneficial non-native fungi is increasingly common due to their positive effects on plant growth, yield, and pathogen suppression. However, this practice may disrupt soil microbial communities, and commercial isolates often show limited adaptation to local conditions. This study aimed to identify native beneficial soil fungi associated with dragon fruit cultivation on the Ecuadorian coast and evaluate their effect on commercial production. Fungal isolates from four dragon fruit plantations were identified using microscopy and genetic sequencing (ITS, EF-1α, and beta-tubulin). The selected fungi were isolates closely related to Talaromyces tumuli, Trichoderma asperellum, and Paecilomyces lagunculariae. All isolates were tested for pathogenicity using detached cladode assays at the laboratory, and non-phytopathogenic monomorphic cultures were further evaluated in the field under a randomized complete block design consisting of T. asperellum, Talaromyces tumuli, a combination of both, and a water control. The combination of T. asperellum and Talaromyces spp. showed a favorable trend in terms of the plants’ vegetative development. However, inoculating Talaromyces tumuli into the commercial plants exhibited a slow response during the first 20 days of the field evaluations. Still, it resulted in a significant increase in the fruit’s diameter and weight, with increases of 88.23% and 67.64%, respectively, compared to those in the control. T. asperellum presented a lower number of fruits per plant, although it showed an increase in fruit diameter and weight. In conclusion, using the native beneficial fungi T. asperellum and T. tumuli contributes positively to the dragon fruit production system.